Maintaining the relation between production and consumption of electricity and heat at decision-making level - Чайковська, Євгенія Євстафіївна (Eastern-European Journal of Enterprise Technologies, 2014)
Known optimization methods of cogeneration systems based on static evaluation of process parameters do not always allow to maintain the relation between heat and electricity production in difficult conditions of inconsistency in their consumption, which requires complicating thermal schemes due to additional equipment. For resource and energy-saving, maintaining the relation between production and consumption of electricity and heat, based on the cogeneration system, which is founded on the integrated dynamic subsystem, including the cogeneration unit, heat pump and battery, is proposed. Using the resulting information, obtained due to operability control and state identification of systems: evaporator-compressor, compressor-condenser of heat pump and operability control and state identification of electric accumulator using mathematical models of the dynamics of the evaporator, compressor, condenser of heat pump and electric accumulator, a method for integrated decision-making in conditions of inconsistency in energy production and consumption is developed. At the change in electricity consumption within the change in co-generation unit capacity, it is possible, by connecting the heat pump, which evaluates both energy production, and its consumption by changing the low-grade energy source temperature, to make pre-emptive decisions on changing the heat production level for further heat carrier use in the cogeneration unit. Forecasting the changes in the battery charge and discharge voltage allows not only to provide economical operation of the heat pump system, but also timely perform economical electro-accumulation during both the unprofitable production of electricity, and decline in its production. Thus, in conditions of maintaining the relation between production and consumption of electricity and heat at the decision-making level, it is possible to reduce energy production cost and harmful emissions of carbon dioxide up to 10–15 %.